Rheological behavior on treated Malaysian crude oil - Chandran, K. (American Institute of Physics Inc., 2016)
Crude oil is always produced with water. This association causes many problems during oil production, arising from the formation of emulsion. Emulsion is an undesirable substance that increases operational and capital cost in the pipeline and processing equipment. To overcome this issue, demulsifiers are formulated to break the emulsion, where they are able to separate the water-oil emulsions to their respective phases. The emulsifier's main function is to reduce the interfacial tension properties of the emulsion. For this research, both the EOR and natural water-in-oil emulsions were treated with low a concentration demulsifier. The main objective of this paper is to determine the dynamic viscosity and rheological properties of the treated EOR and natural emulsion. The dynamic viscosity was obtained using the Brook-field Digital Viscometer. The components that influence the emulsion's rheological properties are the temperature, shear rate and shear stress. The results obtained demonstrate that the viscosity of the treated crude decreases and portrays the Non-Newtonian shear thinning "pseudo-plastic" behavior. Besides that, to determine the interfacial film of the treated crude, the spinning drop tensiometer was used. With the addition of demulsifier, the thinning rate of the oil film accelerates whereby there is a linear decrease in the interfacial tension with an increase in time. Therefore, from the results, it can be observed that the rheology study plays a significant role in the demulsification test. Furthermore, both the rheology approaches showed that time, temperature, shear rate and shear stress have a great impact on the viscosity behavior as well as the IFT. Â© 2016 Author(s).